2015
DOI: 10.1016/j.chiabu.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up approaches to strengthening child protection systems: Placing children, families, and communities at the center

Abstract: Efforts to strengthen national child protection systems have frequently taken a top-down approach of imposing formal, government-managed services. Such expert-driven approaches are often characterized by low use of formal services and the misalignment of the nonformal and formal aspects of the child protection system. This article examines an alternative approach of community-driven, bottom-up work that enables nonformal-formal collaboration and alignment, greater use of formal services, internally driven soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 8 publications
6
98
1
5
Order By: Relevance
“…In the psychosocial field, practice and policy statements now frequently signal that local resources and agendas should be the foundation for interventions (CPWG, 2014;UNICEF, 2015). 'Community-based child protection mechanisms' are increasingly seen as the key resource supporting children's well-being in a culturally appropriate and sustainable manner (Wessells et al, 2012;Wessells, 2015). What sources of data can facilitate deeper understanding of such community resources and mechanisms?…”
Section: For Measuring the Mental Health And Psychosocial Wellbeing Omentioning
confidence: 99%
“…In the psychosocial field, practice and policy statements now frequently signal that local resources and agendas should be the foundation for interventions (CPWG, 2014;UNICEF, 2015). 'Community-based child protection mechanisms' are increasingly seen as the key resource supporting children's well-being in a culturally appropriate and sustainable manner (Wessells et al, 2012;Wessells, 2015). What sources of data can facilitate deeper understanding of such community resources and mechanisms?…”
Section: For Measuring the Mental Health And Psychosocial Wellbeing Omentioning
confidence: 99%
“…Ensuring a diversity in community perceptions is critical, as on many issues there are bound to be differences, at some level, within community perceptions and practices, based on variables such as gender, age, education, ability vs. disability, class and access to power (see Chambers, 1997;Korbin, 1981;Wessells, 2015). As Wessells (2015) found in his own study, many child protection programmes identify community leaders with whom they work to implement a programme of action relating to child protection. However, he argues that 'this approach is problematic because quite often there are marginalised people, including children and the poorest of the poor, who either do not attend such gatherings or remain voiceless when they do attend' (p.12).…”
Section: Accessing Community Starting Points: Strategies For Effectivmentioning
confidence: 99%
“…In the child protection literature the idea of community ownership has also been identified as key to effective programming. Wessells (2015) who, in a paper based on a global review of community-based child protection mechanisms conducted in 2009, identified seven factors that contributed to the effectiveness of such programme, the most important of which was community ownership. Specifically, the review found that "the level of community ownership was higher when people identified the work as 'ours' and took responsibility for its effectiveness" (Wessells, 2015: 11).…”
Section: Embedding Interventions Within Communities: the Importance Omentioning
confidence: 99%
See 2 more Smart Citations